Efficacy of an anhydrous stannous fluoride toothpaste for relief of dentine hypersensitivity: A randomized clinical study. (8th June 2020) - Tao, Danying; Ling, Martin R.; Feng, Xi‐ping; Gallob, John; Souverain, Audrey; Yang, Wenjie; Alavi, Anousheh
Abstract: Aim: To compare efficacy of an anhydrous 0.454% w/w stannous fluoride/sodium fluoride toothpaste (Test) versus a sodium monofluorophosphate toothpaste (Negative control) and a stannous chloride/sodium fluoride toothpaste (Positive control) for dentine hypersensitivity relief after 8 weeks' twice‐daily use. Materials and Methods: In this randomized, examiner‐blind, stratified, parallel study, primary and secondary efficacy variables were mean changes in Schiff score (evaporative [air] sensitivity) and tactile threshold (Yeaple probe), respectively, from baseline to Week 8 between Test ( n = 62) and Negative control ( n = 62). Test and Positive control ( n = 61) comparisons were exploratory objectives. Results: All groups significantly improved from baseline on both dentine hypersensitivity measures ( p < .0001). Difference between adjusted mean changes from baseline in Schiff sensitivity scores at Week 8 for Test versus Negative control groups was 0.19 (95% CI 0.002, 0.374), in favour of the Negative control ( p = .0476; 12.57% difference). Difference in tactile threshold was −7.20 g (95% CI −16.376, 1.975), and this was not statistically significant ( p = .3715; −21.83% difference). Test group showed no significant difference versus Positive control for either measure. Toothpastes were generally well tolerated. Conclusion: While twice‐daily use of Test toothpaste significantly reduced dentine hypersensitivity from baseline, there was no significant advantage over negative or positive controls. Study registration: Clinicaltrials.gov; NCT03310268.